Melanocytic nevi in children: A clinical study - Senthilkumar M; Thappa Devinder (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND: Melanocytic nevi show different presentations in children which have not much studied in India. PURPOSES: To document the incidence and pattern of melanocytic nevi in children. METHODS: A total of 4,256 paediatric cases attending the dermatology OPD, JIPMER during the study period from August 2002 to August 2004 were screened for melanocytic nevi. FINDINGS: Out of these, 41 (0.96%) cases were found to have melanocytic nevi. The mean age of these cases was 1.4 years (range of 3 days to 14 years). Fourteen (34.1%) of them were males and 27 (65.9%) were females with male to female ratio of 1:1.9. Majority of these cases (32 cases, 78%) were in the age group of 0-1 year. Thirty-seven (90.2%) cases had single lesion and 4 (9.8%) cases had multiple lesions. The size of the nevi varied from 1.5 cm to 20 cm in 40 (97.6%) cases and more than 20 cm in 1 (2.4%) case. The most common site of involvement was the back (32 cases, 78%) followed by head and neck (6 cases, 14.6%). Out of the total of 41 cases, 30 (73.2%) were Mongolian spots, 8 (19.5%) were congenital melanocytic nevi, one case (2.4%) each had giant congenital melanocytic nevus, nevus spilus and nevus of Ota. Four cases had other associated cutaneous disorders. These included ashleaf macules in 2 cases, epidermolysis bullosa simplex in 1 case and a solitary case had both cafι-au-lait macule and mixed hemangioma. The systemic associations included seizures (suspected neurocutaneous melanosis) in a solitary case of congenital melanocytic nevi. CONCLUSIONS: The spectrum of melanocytic nevi seen in children in this study partially differs from this of abroad studies. LIMITATION: Unicentre hospital-based study which cannot be generalized.